Perspectives of Parents in Jabodetabek on Indonesia’s 2022 Limited Face-to-Face Learning Policy - Sintapertiwi, Dhian (UIII Press, 2023)
The Indonesian government has announced that their latest policy on limited face-to-face learning will be implemented in January 2022. This policy will be applied equally to all educational levels – from early childhood to tertiary institutions. The latest policy will be unlike the previous ones and will require all students to attend the face-to-face learning. The new changes triggered different opinions among parents who are considered to be one of the key stakeholders in decision making process. During the Covid-19 pandemic, parents had the right to decide to whether or not to send their children back to school. This qualitative study aims to explore parents' viewpoints on the limited face-to-face learning policy that will be implemented in 2022. The data was collected from 20 parents in Jabodetabek (Jakarta-Bogor-Depok-Tangerang-Bekasi) area using Google Form. Semi-structured interviews were also conducted with five parents. The data gathered from the questionnaire showed that most parents agreed to send their children back to school. Health protocols, learning loss, and mental health or well-being were the three themes that emerged as the reasons why parents supported the government’s policy to reopen the schools next year.